Хетто-цупанийские переселенцы и их боги на севере Урарту - Тирацян, Нвард (Зангак-97)
In the Urartian inscriptions of the Ararat plain two gods are mentioned, which we do not meet in the other regions of the Armenian Highland: I(u)arša and AMAR.UTU (ideographic rendering of the the supreme Babylonian god Marduk). Those gods, apparently, were brought to the Ararat plain by the Luwian inhabitants of the lands Hatti and Supani settled there by Argišti I at the foundation of the fortress of Erebuni. I(u)arša may be identified with the Luwian god I(y)ariš, while AMAR.UTU in the Luwian tradion represents the god Šantaš.
Keywords: История